La comunicación y el humor como herramientas para el desarrollo profesional - Palma Heinicke, Carlos Daniel (2022)
Carlos Palma is a multifaceted communicator with great comedy skills on it’s different platforms, television, theater, radio, standup comedy, among others. This has allowed him to develop as a host in these media, standing out at the local level, managing to position himself in the most important communication companies at the national level. In addition, Carlos has been able to develop his skills as a communicator and producer and use his talent to become an entertainment entrepreneur in Peru, creating the main company dedicated to comedy in the country and later one of the content generators in digital media.